Effect of pre-cooling agent on intensity of pricking pain at intraoral injection site in adults: An experimental study. - Munazza Aziz; Shahbaz Ahmed; Fazal-ur-Rehman Qazi; Farah Naz; Marina Shah; Prena Moorpani (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effect of pre-cooling agent on the intensity of pricking pain at the intraoral injection site in adult patients. Method: An in-vivo interventional study, using split-mouth technique was conducted in the Department of Operative Dentistry, Dr. Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, DUHS, Karachi, between September 2018 to August 2019. Total 152 adult patients meeting the inclusion criteria were selected, and consent form was signed to investigate the pricking pain perception during needle administration. Topical anesthesia (benzocaine gel) was applied on left side (control) for 1 min whereas on the experimental (right) side the refrigerated cartridge was placed for 2 minutes. Infiltration anesthesia was then administered on both sides respectively. Patient’s pain perception ratings were measured through Visual analog scale (VAS). After profound anesthesia was achieved, restorative treatment was performed under rubber dam isolation. Statistical analysis was done using SPSS Version 24. Results: The effect of pre-cooling agent i.e. refrigerated cartridge, was statistically significant (P-value <0.05) on the intensity of pricking pain at the intraoral injection site among the age group of 41 to 50 years and female participants of 21to 30 years whereas the effect of pre-cooling agent was found statistically insignificant among the male participants of the age group of 21 to 30 years and irrespective of gender within 31 to 40 years of age. Conclusion: Pre-cooling agent was found effective in decreasing pricking pain sensed by the patients. Precooling agent can be used without topical anesthesia before administering infiltration because cryoanesthesia Continuous...